2003
DOI: 10.1038/sj.ejcn.1601717
|View full text |Cite
|
Sign up to set email alerts
|

Short-term repeatability of a food frequency questionnaire in New Zealand children aged 1–14 y

Abstract: Objective: To evaluate the repeatability of a children's food frequency questionnaire (FFQ) by gender, ethnicity, and age group. Design: A 117-item FFQ asking about food intake patterns over the past 4 weeks was developed using food records from 428 children (204 boys and 224 girls) and the reproducibility on average 13 days apart was tested in 130 children (78 boys and 52 girls). Children were recruited using clustered probability sampling (n ¼ 103), and a convenience sample of 25 Maori children. Setting: Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
41
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 14 publications
10
41
1
Order By: Relevance
“…The final score of the modified MEDFICTS exhibited moderate testeretest reliability (r¼0.36; P¼0.02) in the grade-six children as a group. This correlation is similar to some, 25 yet lower than other, 26 testeretest studies in children, but considerable differences in research contexts, study designs, and outcome measures can explain this. Previous review studies have shown that reliability correlations for food frequency questionnaires among school-age children vary considerably, 27,28 confirming instrument and setting effects.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The final score of the modified MEDFICTS exhibited moderate testeretest reliability (r¼0.36; P¼0.02) in the grade-six children as a group. This correlation is similar to some, 25 yet lower than other, 26 testeretest studies in children, but considerable differences in research contexts, study designs, and outcome measures can explain this. Previous review studies have shown that reliability correlations for food frequency questionnaires among school-age children vary considerably, 27,28 confirming instrument and setting effects.…”
Section: Discussionsupporting
confidence: 75%
“…26,31 In most studies among schoolchildren the first measurement of dietary intake gave higher values than the second. 27 Here our findings tended to differ.…”
Section: Discussionmentioning
confidence: 99%
“…There have been reports on sex/gender differences in reproducibility of FFQs in adults and self-reporting children and adolescents; however, in general, results are not conclusive. 7,8,17,18,23 One possible explanation of our results might be the fact that we used proxy reports on diet. When parents and other proxies report on the children's intakes, it is possible that the sex of the proxy is more important than the sex of the child.…”
Section: Discussionmentioning
confidence: 83%
“…Previous studies from the United States of America, New Zealand and Belgium that have reported reproducibility of food intakes derived from FFQs in children show a wide range of correlation coefficient values ranging from 0.24 to 0.82. [17][18][19][20] Design of the FFQs, statistical methods, data management and the time between first and second administrations vary in these studies, making it difficult to directly compare results. Nevertheless, they give some indication of the typical range of correlation coefficients.…”
Section: Discussionmentioning
confidence: 99%
“…The pilot testing was to assess the acceptability of the 24-h record-assisted recall computerized programme, anthropometric measurements, socio-demographic, physical activity, food security and medical history questions, and the repeatability of the FFQ (Metcalf et al, 2003). Starting points (addresses) were randomly selected with probability proportional to mesh block size in prescribed areas by Statistics New Zealand.…”
Section: Recruitment Of Childrenmentioning
confidence: 99%